Use of non-formal spaces in science teaching: valuation of the rural environment and transformation of raw material - rice culture (Research, Society and Development, 2022)
The study aimed to verify and understand the process of chemical and physical transformation of rice through an investigative expedition in a non-formal institutionalized space, a rice processing company, in the municipality of Agudo/RS. The study considered the contributions of the use of a non-formal space, as a motivation strategy, complementing the proposed contents, as well as contributing to scientific literacy and arousing interest and curiosity in science. The methodology is based on qualitative research, of the case study type, developed in the Science discipline with students from the 9th year of elementary school - final years of the Municipal School of Elementary Education Alberto Pasqualini, in the municipality of Agudo/RS. The actions developed comprised three stages: the theoretical study; investigative expedition and knowledge production; and analysis of results. In view of the results, we believe that the students were motivated to go beyond the school space, to exercise observation, experimentation, and investigation, since the use of non-formal spaces in science teaching, through investigative expeditions, is fundamental in the process of teaching and learning; and this was seen by the students as a different and more dynamic class; contributed to scientific initiation, awakening curiosity and motivation for research; understand and interpret the world around them; and even in this case, to understand concepts of Matter, associated with the culture and processing of rice and the valorization of agriculture and the rural environment.